Roofing sheets systems for industrial sheds in cyclone prone areas based on dynamic testing - Narayanan, S.P. (Construction Research Institute of Malaysia, 2014)
Rooing sheets of industrial sheds have been observed to fail in uplift under extreme wind conditions as in a cyclone. The ultimate loads from full scale static uplift load tests on asbestos cement and galvanized iron corrugated rooing sheet systems with different connections for span/purlin spacing of 1.4 m used in India using gravity load method were used to arrive at suitable connections for different wind zones. Since suitable rooing systems are not available for AC single span (case 1) and for Asbestos Cement (AC) and Corrugated Galvanized Iron (CGI) single and double span (case 2), static tests were done reduced spans and suitable spans were identiied. Fatigue is a major factor contributing to failure of rooing systems in the cyclone prone Eastern coastal zone. The rooing systems selected based on static tests were subjected to simulated dynamic tests which simulate low-high-low load cycles during a cyclone, ensuring that the frequency of load application does not coincide with natural frequency of rooing sheet system. If failure occurs, smaller spans are tested. For testing single and two span rooing sheets the two-point load systems and midspan load systems respectively were used. Based on the tests, suitable reduced spans are recommended for these zones. General guidelines to be followed while ixing AC and CGI rooing sheet systems are also given.